2007
DOI: 10.1080/18811248.2007.9711288
|View full text |Cite
|
Sign up to set email alerts
|

Vibro-Packing Experiment of Non-Spherical Uranium Dioxide Particles with Spherical Metallic Uranium Particles

Abstract: Japan Atomic Energy Agency has developed vibro-packed fuel as one of the candidates for commercial fast breeder reactor fuels. In this study, vibro-packing experiments were carried out to investigate particle movement during vibro-packing as well as particle distribution after the completion of vibro-packing. Non-spherical uranium dioxide particles and spherical metallic uranium particles were used to simulate mixed oxide particles and oxygen getter particles, respectively. These experiments revealed the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Ott et al (2009) have reported two benchmark problems related to MOX fuel performance based on fuel modeling codes where they have studied the effect of rod power density on fuel centerline temperature and fuel pin pressure. Matsuyama et al have measured the axial distribution of bulk density of vibro-packed spherical metallic uranium particles mixed with non-spherical uranium dioxide particles using X-ray transmission radiography experiments (Matsuyama et al, 2007). Image processing techniques based on Sobel edge detection filters were applied for detection of carbon deposition thickness on the surface of the cladding.…”
Section: Introductionmentioning
confidence: 99%
“…Ott et al (2009) have reported two benchmark problems related to MOX fuel performance based on fuel modeling codes where they have studied the effect of rod power density on fuel centerline temperature and fuel pin pressure. Matsuyama et al have measured the axial distribution of bulk density of vibro-packed spherical metallic uranium particles mixed with non-spherical uranium dioxide particles using X-ray transmission radiography experiments (Matsuyama et al, 2007). Image processing techniques based on Sobel edge detection filters were applied for detection of carbon deposition thickness on the surface of the cladding.…”
Section: Introductionmentioning
confidence: 99%